Jóvenes universitarios y sostenibilidad ante el ocio digital - Reglero Rada, Mercedes; Marquès Donoso, Albert (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
This article analyzes technology consumption and its relationship with sustainability among university students. the study is based on a survey that assesses the time spent on internet-connected devices, technological dependence, and anxiety related to a lack of access to social networks. additionally, knowledge about the environmental implications of using digital devices, such as charging mobile devices, is explored. the results reveal high technology consumption, with an average of nearly 7 hours per day dedicated to internet-connected devices. this excessive consumption is associated with con stant energy dependence and the need to replace obsolete devices, raising concerns about sustainability. in terms of environmental awareness, there is a moderate level of knowledge about the environmental implications of charging mobile devices and the traceability of the environmental footprint. Most of the respondents express concern about the environmental footprint, indicating a growing awareness among the university student population about the environmental implications associated with technology.
Keywords: sustainability; eco-anxiety; technological addiction; social responsibility